Pengaruh Stres Kerja Dan Motivasi Kerja Terhadap Turnover Intention Karyawan CV. Sollu Citra Muslim - Karmita Karmita; Rita Tri Yusnita; Mila Karmila (STIKes Ibnu Sina Ajibarang, 2023)
This study aims to determine and analyze the effect of work stress and work motivation in CV. Sollu Muslim Image and Its Influence on Turnover Intention. This research model uses a survey method with a causality research design. Data collection techniques were carried out by distributing questionnaires to CV employees. Sollu Citra Muslim as many as 63 people. Data analysis technique using Path Analysis. Based on the results of the study it is known that work stress and work motivation have a negative and not significant direct effect on turnover intention. Both Work Stress and Work Motivation have a negative and not significant direct effect on Turnover Intention. Therefore it is suggested that companies can increase back Work Stress, Work Motivation and Turnover Intention so that they can have a positive impact and achieve company goals in the future.